Climate cover-up the crusade to deny global warming - Hoggan, James 1946-; Littlemore, Richard (Vancouver Greystone Books, 2009)
This is a story of betrayal, selfishness, greed and irresponsibility on an epic scale. Hoggan examines the public relations circus that surrounds global warming, and uncovers the organized campaign, largely financed by the coal and oil industries, to make us think that climate science is still somehow controversial.
Lemmings and lifeguards : keeping humankind from crashing on the rocks -- The inconvenient truth : who says climate change is a scientific certainty? -- From Bernays to today : a brief history of private prophets and public lies -- The age of astroturfing : in which industry steals credibility from the people -- Internationalizing uncertainty : taking the doctrine of doubt on the road -- Mangling the language : making doubt reliable and science unbelievable -- Think tank tactics : moving public policy into private hands -- Denial by the pound : many wrongs don't make a right, but they sound better -- Junk scientists : an expert for every occasion, an argument for every position -- From denial to delay : a more reasonable--and more dangerous--trend in obstructing action on climate change -- Slapp science : using courts and cash to silence critics of climate confusion -- Manipulated media : an industry overwhelmed in the age of information -- Money talks : calculating the heavy weight of political capital -- Whitewashing coal : in coal country, cleanliness is relative, but profit is absolute -- Little coal : salvaging a future that's stuck in the tar sands -- Nobody wants to be a chump : how the debate cripples public policy and paralyzes private action -- Saving the world : tactics for turning back the clock on global disaster.
Includes bibliographical references (p. [237]-240)and index.
Keywords: Climatic changes; Climatic changes -- Government policy